Translating Love: An Analysis of Love Languages and Translation Techniques in Aku Jati Aku Asperger - Arbain, Arbain (STAIN Majene, 2025)
This study examines how love languages are expressed and translated in the Indonesian film Aku Jati Aku Asperger, focusing on the maintenance of emotional meaning across cultural and linguistic boundaries. The research aims to identify how different forms of affection are represented in the film and how translation techniques contribute to preserving emotional authenticity in the English subtitles. Using a qualitative descriptive method, the study analyzes Indonesian dialogues and their English translations to examine the relationship between linguistic choice and emotional expression. A total of 110 dialogue units were selected and categorized based on five types of love languages: Words of Affirmation, Acts of Service, Receiving Gifts, Quality Time, and Physical Touch. The analysis reveals that Words of Affirmation appear most frequently, reflecting the direct and sincere emotional style of the main character, followed by Acts of Service and Quality Time. The most frequently applied translation techniques are literal translation, established equivalent, and modulation, which help maintain both linguistic clarity and emotional resonance. These techniques ensure that the translated dialogues convey similar levels of empathy and intimacy as the original. The study highlights that effective film translation requires not only linguistic accuracy but also emotional sensitivity to achieve meaningful cross-cultural communication.